A spiritual contact zone. Re-inventing Ritual Space in The Netherlands' Afrika Museum - Kleuskens, Elise (Jaarboek voor liturgieonderzoek, 2010)
The research project Holy Ground, led by Paul Post and Arie Molendijk, has drawn attention to the process of ‘re-inventing ritual space in modern Western culture’ by examining various places, such as ‘rooms of silence and memorial shrines for victims of disease and violence’.2 Here we want to address ‘the art museum as a ritual site’,3 especially with regard to a major exhibition that sought to bring religious experiences across.